miR-3200 accelerates the growth of liver cancer cells by enhancing Rab7A - Shuting Song; Sijie Xie; Xinlei Liu; Shujie Li; Liyan Wang; Xiaoxue Jiang; Dongdong Lu (Non-coding RNA Research, 2023)
Researches indicate miR-3200 is closely related to tumorigenesis, However, the role of miR-3200 in human hepatocarcinogenesis is still unclear. In this study, we clearly demonstrate that miR-3200 accelerates the growth of liver cancer cells in vivo and in vitro. Obviously, these findings are noteworthy that miR-3200 affects the transcriptional regulation for several genes, including DSP，BABAM2, Rab7A,SQSTM1,PRKAG2,CDK1,ABCE1,BECN1,PTEN,UPRT. And miR-3200 affects the transcriptional ability of several genes, such as, upregulating CADPS, DSP,FBXO32, PPCA,SGK1, PATXN7L1, PLK2,ITGB5,FZD3,HOXC8,HSPA1A,C-Myc,CyclnD1,CyclinE,PCNA and down –regulating SUV39H1, MYO1G, OLFML3, CBX5, PPDE2A, HOXA7, RAD54L, CDC45,SHMT7,MAD2L1,P27,IQGAP3,PTEN,P57,SCAMP3,etc...On the other hand, it is obvious that miR-3200 affects the translational ability of several genes, such as, upregulating GNS,UPRT,EIFAD,YOS1,SGK1,K-Ras,PKM2,C-myc,Pim1,CyclinD1,mTOR,erbB-2,CyclinE,PCNA,RRAS,ARAF,RAPH1,etc.. and down-regulating KDM2A, AATF, TMM17B, RAB8B, MYO1G,P21WAF1/Cip1,GADD45,PTEN,P27,P18,P57,SERBP1,RPL34,UFD1,Bax,ANXA6,GSK3β. Strikingly, miR-3200 affects some signaling pathway in liver cancer, including carbon metabolism signaling pathway, DNA replication pathway, FoxO signaling pathway, Hippo signaling pathway, serine and threonine metabolism signaling pathway, mTOR signaling pathway, Fatty acid biosynthesis signaling pathway, carcinogenesis-receptor activation signaling pathway, autophagy signaling pathway. Furthermore, our results suggest that miR-3200 enhances expression of RAB7A, and then Rab7A regulates the carcinogenic function of miR-3200 by increasing telomere remodeling in human liver cancer. These results are of great significance for the prevention and treatment of human liver cancer.